Pertanggungjawaban Pidana dalam Honor Killing: Pendekatan Atribusi Peran Pelaku - Zul Khaidir Kadir (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Honor killing cases often involve a distributed structure of perpetrators between decision-makers, providers of means, and implementers. This collective pattern raises the problem of role attribution in criminal law enforcement, which often shifts toward two problematic tendencies: centralizing responsibility on the executor or expanding criminal responsibility based on family ties. This article aims to formulate a tested role attribution model so that criminal responsibility does not stop at the direct perpetrator and does not develop into association-based punishment. This research uses a normative legal research method with a conceptual approach. Data collection methods were collected using literature studies, then analyzed qualitatively and presented descriptively. The research results formulate a role map of instigator, facilitator, and executor, operationalized through group role attribution based on two axes: causal contribution and normative contribution. The instigator is understood as the driver who shapes the will and locks the decision, the facilitator is understood as an assistant who deliberately provides the opportunity, means, or information. Meanwhile, the executor is someone who carries out the material act, although in terms of position, their actions are not automatically identical to the dominance of the decision. This division of roles is complemented by evidentiary indicators covering communication, financing, provision of facilities, field control, and post-incident intimidation, along with negative criteria to prevent inferences based on blood relations or passive presence. This model provides a more measurable standard of attribution for investigation, prosecution, and sentencing in collective honor killing cases.